Towards a solidary form of publicness: Circulation of cultural assets between alternative cultural organizations of Istanbul and their micro public(s) - Sanul, Gökçe (2020)
One of the world’s mega cities, Istanbul is changing drastically with the neoliberal and conservative policies transforming its public spaces and sociocultural fabric in contested ways. These changes require stimulating reflections on the formation of new public spheres. This paper approaches this problematic through a focus on the ways in which alternative cultural organizations in Beyoğlu- the cultural hub of Istanbul-create new forms of publicness. Drawing on a comprehensive empirical research, this paper argues for a solidary form of publicness developing in and through alternative cultural organizations of Istanbul via the circulation of cultural assets. This particular form stimulates a thinking about publicness as circulation going beyond the too simple idea of the physical togetherness of people in one particular place. Instead, it aims to reconceptualize publicness through the solidarity relations of alternative cultural organizations and their micro public(s) and to observe the formation of multiple (counter) public spheres as an emergent infrastructure of circulation connecting different sites, people and media across cultural spaces.